In-situ hydrodeoxygenation of lignin via hydrothermal liquefaction with water splitting metals: Comparison between autocatalytic and non-autocatalytic processes. (5th February 2022) - Wang, Jian; Liu, Zibiao; Li, Jian; Yan, Beibei; Tao, Junyu; Cheng, Zhanjun; Chen, Guanyi
Abstract: In this study, various water splitting metals (Mg, Al, Zn, and Fe) were investigated for lignin HDO-HTL. Their behaviors during autocatalyzed hydrogenation and interactions with Al–Ni alloy catalyst during non-autocatalyzed hydrogenation were studied. The relationships between Mg, Zn, and Fe with Al–Ni catalyst were synergistic in HTL for bio-oils generation, leading to higher bio-oil yields in non-autocatalytic process than in autocatalytic process and Al–Ni catalytic HDO process. In contrast, because the effect of γ-AlO(OH) was strengthened when Al was used, the coking phenomenon was induced, leading to an antagonistic effect towards bio-oil production. Additionally, although the production of hydrogen was the lowest when Fe was applied, the bio-oil yields reached the highest (44.53 wt% in non-autocatalytic process and 49.83 wt% in autocatalytic process, respectively) with the deoxygenation degrees of 8.41% in non-autocatalytic process and 9.75% in autocatalytic process. Accordingly, Fe exhibited significant potential in lignin in-situ HDO-HTL. Graphical abstract: Image 1 Highlights: In-situ HDO-HTL of lignin using water splitting metals were firstly investigated. Mg, Zn and Fe as water splitting metals showed synergetic effects with Al–Ni. Fe showed optimal bio-oil yields in autocatalytic and non-autocatalytic processes. Active hydrogen maybe a key factor that affect the performance of in-situ HDO-HTL. The DOD of autocatalytic and non-autocatalytic processes on Fe were 8.41% and 9.75%.